Quality-checking a novel “fact sheet” on ghostly episodes - Massullo, Brandon Jon; Houran, James; Escolá Gascón, Alex; O’Keeffe, Ciarán; Drinkwater, Kenneth Graham; Dagnall, Neil (Frontiers in Psychology, 2025)
Introduction‘Apparitions, hauntings, and poltergeists’ are universally reported phenomena with significant psychological and social implications. Despite their prevalence, the scientific study of these anomalous experiences remains fragmented, and misinformation is widespread. To address this gap, a resource titled “Fact Sheet: Ghostly Episodes at a Glance” was developed to provide an evidence-based summary for educational and clinical use.MethodsThis preliminary study evaluated the Fact Sheet’s content validity through an AI-based verification procedure. Additionally, we assessed its accessibility, utility, and global favorability among four groups: lay percipients, lay non-percipients (information-seekers), clinical practitioners, and amateur paranormal investigators (information-providers).ResultsThe Fact Sheet demonstrated strong content validity, accessibility, usefulness, and favorability across all groups. However, participants suggested refinements to enhance readability and contextual depth. Statistical analysis revealed small but significant differences in global favorability scores, with information-providers more strongly endorsing the resource than information-seekers.ConclusionThese findings underscore the importance of scientifically-grounded, accessible resources in educating diverse audiences about anomalous experiences. The study highlights the value of data-driven public education in this domain and offers specific recommendations for improving future iterations of the Fact Sheet to boost engagement and comprehension in both educational and clinical settings.